State-selective charge exchange from H(1s), H(n = 2), Li and Na targets by very highly charged ions - Otranto, Sebastián (2010)
In order to provide information for charge exchange spectroscopy diagnostics in new, high temperature tokamak plasmas, n-level state-selective electron capture cross sections are presented for very highly charged ions with charge states q 10. Fully stripped ions with charges of 10+, 18+, 26+, 54+ and 92+ are considered in order to provide scaling information over a broad range. The H(1s) and H(n = 2) targets are evaluated at 1, 10 and 100 keV/amu, i.e. plasma core temperatures to those encountered during neutral beam heating. For use in pellet diagnostics, cross sections are given for Li and Na targets at 10 keV/amu. These latter targets also provide a means to experimentally test the accuracy of the H(n = 2) results since they are pseudo-one-electron atoms with ionization energies close to that of excited hydrogen.